Implementation of The Village Community Development and Empowerment Program through Priorities of the Use of Village Funds in the Coastal Area, Aceh Barat Regency - Nurhaslita Sari; Arfriani Maifizar (Sociology Department Of Syiah Kuala University, 2023)
This study aims to investigate the effectiveness of the Village Community Development and Empowerment Program (P3MD) in the coastal areas of West Aceh Regency, with a focus on the priority use of village funds. Specifically, the study explores the changes in the community's economy before and after the implementation of village funds and examines the initiatives taken by the village government to enhance economic conditions. Descriptive analysis is employed as the analytical method to evaluate the outcomes. This study shows that the policy assistance of the Village Community Development and Empowerment Program in West Aceh Regency has not yet achieved optimal effectiveness in its implementation. This can be observed from the three approaches used to measure the effectiveness of mentoring in P3MD in Aceh Barat District. Two indicators, including the source approach and the target approach, have not worked well. In the future, policy implementers need to focus more on optimizing resources and involving a wider range of target groups.